2015
DOI: 10.1002/ange.201501122
|View full text |Cite
|
Sign up to set email alerts
|

Eine Iod‐katalysierte Hofmann‐Löffler‐Reaktion

Abstract: Iodreagentien werden als çkonomischu nd çkolo-gischa nsprechendeA lternativen zu Übergangsmetallen aufgefasst, obgleichi hr Einsatz als molekulare Katalysatoren in anspruchsvollen C-H-Oxidationen weitgehend ausgeblieben ist. Hier wird eine attraktive Iodoxidationskatalyse vorgestellt, die eine bequeme Umwandlung von Kohlenstoff-Wasserstoffin Kohlenstoff-Stickstoff-Bindungen mit bislang unerreichter vollständiger Selektivität ermçglicht. Die Reaktion verläuft innerhalb zweier miteinander verflochtener Katalysez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The corresponding structures of compounds 3f, 3g, 3i and 3k are depicted in Figure 2 [17] andc ompliment the one of compound 3e reported earlier. [12] The key features of these compoundsa re 1) the expected linear coordination mode of the anionic carboxylates at the central iodine atom and 2) the rather short iodine-oxygen bond lengths in the range of 2.16 to 2.20 .T his demonstrates as horter bonding and thus stronger interaction for the anionic ligandst han in comparable pyridine (2.255-2.261 ) [18][19][20] and DMSO adducts (2.27 ). [11] Iodine reagents 3 display ar emarkable stability in solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding structures of compounds 3f, 3g, 3i and 3k are depicted in Figure 2 [17] andc ompliment the one of compound 3e reported earlier. [12] The key features of these compoundsa re 1) the expected linear coordination mode of the anionic carboxylates at the central iodine atom and 2) the rather short iodine-oxygen bond lengths in the range of 2.16 to 2.20 .T his demonstrates as horter bonding and thus stronger interaction for the anionic ligandst han in comparable pyridine (2.255-2.261 ) [18][19][20] and DMSO adducts (2.27 ). [11] Iodine reagents 3 display ar emarkable stability in solution.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reportedt he synthesis of such an ew stable iodine(I) compound, which represents the tetrabutylammoniumd erivativeo ft he catalyst resting state in an iodine catalyzed Hofmann-Lçffler reaction. [12] Evidently,i nt his type of CÀHa mination reactiont he specific reactivity of the electrophilic iodine(I) reagent gives rise to an N-iodination, which is the origin of the requiredr adical-based reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Our strategy for g-functionalization is inspired by the modern resurgence of interest [8,9] in the Hofmann-Lçffler-Freytag (HLF) [10][11][12] reaction. In traditional HLF processes, position selectivity arises based on formation of an intermediate nitrogen-centered radical that engages in a1,5-HAT process [13] through ak inetically favored, six-membered transition state.…”
mentioning
confidence: 99%
“…[4] Meanwhile,a lthough much efforts have been paid on the fluorination of carbonyl compounds,m ost reactions are restricted to the synthesis of a-fluoro carbonyl compounds. [7] Among them, fluorinated iodines(III) acting as the highly reactive electrophilic fluorinating reagents have been employed for the fluorination of alkenes,s uch as fluorooxygenation, [8] fluoro-amination, [9] and difluorination [10] of alkenes.I nt hese reactions,t he key iodonium complex int.I was formed initially,f ollowed by sequential double S N 2t ype nucleophilic substitution processes to give final functionalized fluorination products (Scheme 1a). [6] Iodine(III) reagents have been extensively applied in organic chemistry,e specially for the difunctionalization of alkenes.…”
mentioning
confidence: 99%
“…The reaction yields could be improved to 60 %b yi ncreasing the amount of [F]-1 (5 equiv,entry 2). Further control experiments revealed that of all the parameters of palladium catalyst, BF 3 ·OEt 2 and CO gas were crucial for the successful transformation (entries [7][8][9]. However,f urther optimizing reaction condition failed to improve yields,b ut with substrate 1a exhausted.…”
mentioning
confidence: 99%